West African kenaf (Hibiscus Cannabinus L.) natural fiber composite for application in automotive industry - Abdullahi, Tijjani; Harun, Zawati; Dzarfan Othman, Mohd Hafiz; Aminu, Nasiru; Gabriel, Oguntunde; Aminu, Tijjani; Ibrahim, Siti Aida; Kamarudin, Noor Hasliza (Penerbit UTM Press, 2018)
The study of the kenaf core fiber – polymer composites was done by preparing a kenaf/polymer composite using polypropylene (PP) polymer matrix and Scona TPPP 9012 GA as coupling agent with Nigerian grown Kenaf natural fiber through hot pressing. The objective was to characterize the stability and bond strength of the polymer/fiber interface through morphological analysis by using Scanning Electron Microscopy (SEM) as well as the characterization of thermal and mechanical properties of the composite. The result obtained shows an increment in tensile strength as a percentage of kenaf fiber increased to 30%, this trend continuous surprisingly, even at 50% kenaf fiber loading, which goes against the result obtained in previous literature. Thus, signifying the positive influence of Scona TPPP 9012 GA coupling agent. However, further analysis indicated that 40% kenaf fiber loading has a better chance to be considered suitable for use in automotive structure.